A new antioxidant made from a pterostilbene functionalized graphene nanocomposite as an efficient treatment for dry eye disease - Lin, Mimi; Sun, Xueqin; Ye, Sihao; Chen, Youyi; Gao, Jing; Yuan, Feng; Lin, Na; Lawson, Tom; Liu, Yong; Deng, Ruzhi (Frontiers in Chemistry, 2022)
Dry eye disease is a common condition that affects the eyes. It is caused by problems with the tear film and the tear dynamics. Dry eye can be caused by an increase in the number of reactive oxygen species (ROS) in the corneal epithelium. The treatment for dry eye typically focuses on relieving the uncomfortable symptoms by using eye drops such as artificial tears, antibiotics, and by using anti-inflammatory/immunosuppressive agents such as cyclosporine, and lifitegrast. However, the recovery of dry eye patients, particularly those that are severe, always takes a couple of years. This is because the present treatment approaches for dry eye are not based on its cause, e.g. the oxidative stress arising from the rapid increase in ROS. This work describes a new type of antioxidant made from pterostilbene (PS) and carboxyl-chitosan modified graphene (CG). The use of a hydrophilic two-dimensional CG nanosheet to improve the properties of PS is reported. Superior enhanced properties including better cellular permeability, long sustained release period (over 30 hrs), and antioxidant properties, were realized by using PS-CG. A hyperosmotic (HS) damaged human corneal epithelial cell (HCEC) model was used for antioxidant tests. This model has an intracellular ROS level 4 times more than that of a control group. The ROS content was declined efficiently to the same amount as normal cells in the PS-CG treated HS group. There was a significant decline in the content of lactate dehydrogenase (LDH) and the apoptosis rate of HCEC in the PS-CG treated HS group when compared to that seen in the HS model. Real-time polymerase chain reaction (PCR) and western blots (WB) were used to understand the antioxidant mechanism of PS-CG. The results showed that the antioxidant was working by activating the Keap1-Nrf2-ARE signalling pathway. The as-prepared PS-CG was confirmed to be an efficient antioxidant by in vivo experiments done on a dry eye mouse model. More tear secret and healthier corneal and conjunctival epithelial cells were achieved when PC-CG was applied to this model. The use of PS-CG could be a new strategy for treating dry eye and other ocular diseases caused by ROS.